WEB-BASED DECISION SUPPORT SYSTEM FOR KPPS MEMBER SELECTION USING SMART METHOD - Faridi, Muhammad Khairul; Mahral Kusuma Hadi (Bulletin of Network Engineer and Informatics, 2025)
General elections constitute a fundamental pillar of democracy, necessitating objective and transparent administration mechanisms, particularly through the Voting Organizing Group (KPPS). This research develops a web-based decision support system (DSS) to facilitate the Voting Committee (PPS) in selecting KPPS members utilizing the Simple Multi-Attribute Rating Technique (SMART) method. The system was designed employing the Waterfall development model with web-based architecture implemented through PHP programming language and MySQL database management system. The findings indicate that the system significantly enhances objectivity and transparency in the KPPS member selection process. The system proves to be effective, readily adaptable, and substantially improves organizational accountability.